Fabrication of visible-light-active Fe-2MI film electrode for simultaneous removal of Cr(VI) and phenol. (15th November 2022) - Tan, Meng; Gao, Qiaoyuan; Fu, Yangjie; Xu, Youran; Hao, Derek; Ni, Bing-Jie; Wang, Qi
Abstract: In this study, a new coordination polymer of Fe-2-methylimidazole (Fe-2MI) was successfully loaded onto F-doped tin oxide (FTO) via a one-pot solvothermal method, using Fe(NO3 )3 and 2MI as raw materials. For X-ray diffraction patterns (XRD) and scanning electron microscope (SEM) analysis, it can be deduced that Fe-2MI assembles were evenly dispersed on the surface of FTO, and were partially encapsulated by tiny FeOOH particles. The as-prepared Fe-2MI film electrode was used as photoanode with titanium sheet (Ti) as the cathode. Simultaneous photoelectrocatalytic (PEC) removal of phenol and Cr(VI) can be effortlessly accomplished under noticeable light illumination. Meanwhile, the impact of initial Fe state was also investigated. Fe-2MI prepared with Fe(III) behaved better PEC performance than that with Fe(II). Furthermore, the Fe-2MI photoanodes were optimized by adjusting the initial concentration of Fe(III) and 2MI precursors. Besides, the application conditions were optimized at acidic pHs and 2.5 V bias voltage. Cr(VI) can be completely reduced with 80% removal of phenol after 5 h PEC reaction. After 5 successive cyclic runs, stable photocatalytic performance can still be observed. Therefore, Fe-2MI coordination polymer can be a promising candidate for preparing visible-light-active photoanode in the application of environmental remediation.